2005
DOI: 10.1002/chem.200400396
|View full text |Cite
|
Sign up to set email alerts
|

Large pKa Shifts of α‐Carbon Acids Induced by Copper(II) Complexes

Abstract: A series of synthetic receptors (4-6) incorporating metal ions, specifically copper(II), were examined for their ability to enhance the acidity of active methylene compounds. The copper(II) complexes were observed to reduce the pKa of 1,3-diketone carbon acids in acetonitrile by as much as 12 pKa units. The relatively large pKa reduction achieved by the complex is attributed to the electrostatic interaction between the anionic pi system of the enolate and the copper(II) ions. The cage structure and hydrogen bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
(40 reference statements)
1
29
0
1
Order By: Relevance
“…As mentioned earlier, calculations have indicated that protonated ␣-carboxyl groups of ␣-amino acids show dramatically reduced (factor of Ϸ10 10 ) pK a s for the ␣-proton (13). The observed electrostatic environment of the ␣-carboxylate likely disperses its negative charge far more effectively than protonation, thereby amplifying this effect (22).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned earlier, calculations have indicated that protonated ␣-carboxyl groups of ␣-amino acids show dramatically reduced (factor of Ϸ10 10 ) pK a s for the ␣-proton (13). The observed electrostatic environment of the ␣-carboxylate likely disperses its negative charge far more effectively than protonation, thereby amplifying this effect (22).…”
Section: Resultsmentioning
confidence: 99%
“…In fact the carboxylate of the ligand must be in the anionic form since protonated a-carboxyl groups of a-amino acids show dramatically reduced pK a for the Ha (by a factor of about 10 10 ) thus preventing the reaction to occur [29]. This effect can be ascribed to the electrostatic environment of the acarboxylate which likely disperses its negative charge stabilizing this form and thus amplifying this effect [30]. Hence, the possible state of protonation for L,L-DAP considered in this study are the classical zwitterionic form (prevalent at neutral pH) and the corresponding basic anionic form (prevalent at pH $ 8).…”
Section: Resultsmentioning
confidence: 93%
“…Physical organic chemistry usually deals with the effects of substituents which are covalently attached to the structure carrying the reactive site. [38] Although many cases of ion-induced pK a shifts are available, [39][40][41][42][43] the concept of photo-ionic triode action is unprecedented. An elegantly tunable fluorescent PET sensor for glucose developed by James and Shinkai [44] does not correspond to photo-ionic triode action.…”
Section: Methodsmentioning
confidence: 99%